تحليل حاجات دارسي اللغة العربية للمهارات اللغوية الاتصالية الشفهية في جامعة العلوم الإسلامية الماليزية والجامعة الإسلامية العالمية في ماليزيا - ماجد محمد عبيد باضاو ي
The issue tackled in this study lies on knowing and determining the linguistics communicative issues as a part of the Arabic language learning process in Malaysia. The study opted to analyze these needs of language communicative skills among those who specialized in the Arabic language for non-native speakers in the targeted universities as well as the challenges, limitation and the level of knowledge surrounding this issue among the students. The study utilizes quantitative method; hence, the researcher relies on the descriptive analytical method on his research through distributing questionnaire to 141 (out of 400, randomly selected) of the third-year students at the degree level in the Universiti Sains Islam Malaysia (USIM) and International Islamic University Malaysia (UIAM). The outcome of the questionnaire has then been analyzed and discussed in detail to answer the research questions using SPSS software. The results indicated that students have various communicative oral issues and needs based on their specific academic program which relate to the Arabic language as offered by their respective institutions. It is also shown that students are aware of their needs of Arabic communication skills and show their efforts to gain the much-needed skills during their study. At the end of study, the researcher came out with a set of recommendations and suggestions to resolve the linguistic communicative oral issue among students who study Arabic language in Malaysia at the higher level.